The distinct pattern of movement disorders in Caspr2 and LGI1 antibody associated autoimmune encephalitis - Goevert, F; Becktepe, J; Balint, B; Varley, J; Irani, S; Titulaer, M; de Vries, J; Joubert, B; Honnorat, J; Rodriguez, HA; Dalmau, J; Deuschl, G; et al. (Wiley, 2019)
Objective: The aim of this study was (1) to investigate the prevalence of movement disorders in a large cohort of patients with encephalitis with LGI1 and CASPR2 antibodies and (2) to compare clinical phenomenology between patients with Caspr2 and LGI1 antibodies. Background: Movement disorders are a common clinical feature in NMDAR encephalitis. However, their frequency and phenomenology in other common antibody‐defined autoimmune encephalitis subtypes is less well studied. Autoimmune encephalitis with antibodies targeting the neuronal proteins LGI1 or CASPR2 are other frequently observed neuronal autoantibodies in patients with autoimmune encephalitis. Methods: Retrospective analysis of 280 patients from 5 different referral centers with encephalitis and antibodies against LGI1 or CASPR2 in serum and/or CSF was performed with a focus on the clinical presence of movement disorders. Results: FBDS were observed in 25.5% of patients with LGI1 antibodies while other movement disorders (chorea 1.9%, myoclonus 1.9%, tremor 0.9%) were rare or absent (ataxia, tics, dystonia and parkinsonism). In contrast patients with Caspr2 antibodies presented significantly more frequent with ataxia (23%, p = <0.0001), myoclonus (12.6%, p = 0.001) and tremor (10.3%, p = 0.001) while chorea (1.7%) and parkinsonism (1.7%) were rare. Prominent myoclonus was found in 22 patients with Caspr2 antibodies. In 2 patients myoclonus was the only clinical finding in the context of Caspr2 autoimmunity while in the remaining patients myoclonus presented in combination with well‐known anti–Caspr2 antibody‐related syndromes. However, myoclonus was the presenting symptom in 40.9% (n=9) patients. Topographically, myoclonus was generalized in 36.4% (n=8), multifocal in 40.9% (n=9 [6 lower limbs, 3 upper limbs]) and segmental in 9% (n=2) of patients. In the majority of patients (59.1%, n=13) myoclonus was aggravated or exclusively triggered by orthostatism (76.9%, n=10) and/or walking (38.5%, n=5). In 27.3% (n=6) myoclonus presented as a pure paroxysmal kinesiogenic movement disorder. Immunotherapy lead to complete allevation or major improvement of myoclonus in 81.8% (n=18). Conclusions: Movement disorders are a common feature in patients with autoimmune encephalitis with LGI1 and CASPR2 antibodies. Interestingly, the pattern of movement disorders differed between patient groups, which could help to guide diagnosis.